Transitivity Analysis of AJ Hogeâ€™s Short Story â€œDay of the Deadâ€ - Alan Jaelani; Ihda 'Abidat; Amalul Umam; Movi Riana Rahmawanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study analyzes a short story created by AJ Hoge, a well-known English Materials creator of effortless English learning with his short story. It aims to reveal how meanings are constructed and what characterizes the story. Transitivity system, a framework of Halliday's Systemic Functional Linguistics (SFL), is used as an analytical tool. The data are gathered from the short story entitled â€œDay of the Deadâ€. This study employs qualitative descriptive analysis incorporating SFL into the methodology and Transitivity system analysis. This study finds that the creator employs all six Process types of Transitivity i.e., Material, Mental, Relational, Behavioral, Existential, and Verbal Processes. In constructing meanings, the six Processes are manifested in the three elements of the story: orientation, sequence of events, and reorientation. The employment of the six Processes is as an effort to expose learner to the clause as representation completely, that is to provide learners with all possible represented experiences through Processes that may happen in the world. The dominant Process of Material becomes the characteristic of the text and meets the linguistic features of recount text.